THE EFFECT OF PROMOTION AND TOURISM FACILITIES ON TOURIST INTERESTS AND ITS IMPACT ON TOURIST LOYALTY IN MANDEH TOURISM AREA (STUDY BASED TOURISM IN MANDEH TARUSAN AREA WEST SUMATERA) - Dori mittra candana; Muhammad Pondrinal; Rio Andhika Putra; Ratih Purwasih (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
This study aims to determine the effect of promotion and tourist facilities on tourist interest and its impact ontourist loyalty in the tourist area of Mandeh. The sample in this study were tourists who visited the Mandehtourist area. This study uses quantitative methods with Structrul Equation Modeling (SEM) Partial Least Square(PLS) analysis tools. The results in this study indicate a positive and significant effect of promotion and tourismfacilities on tourist interest. Promotion and tourism facilities have no significant effect on tourist loyalty. Thereis also a positive and significant influence of tourist interest on tourist loyalty. Meanwhile, there is a positiveand significant influence of promotion and loyalty through tourist interest. And there is a positive and significantinfluence on tourism facilities and loyalty through tourist interest